2005
DOI: 10.1089/thy.2005.15.1245
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Incision Infiltration of Local Anesthetic Reduces Postoperative Pain with No Effects on Bruising and Wound Cosmesis After Thyroid Surgery

Abstract: Optimizing postoperative pain control is an important aspect in perioperative patient care. The aim of this study was to investigate the efficacy of preincision local anesthetic infiltration in postoperative pain management for thyroid surgery and its relationship to bruising and wound cosmesis. In a randomized single-blinded study, 39 consecutive patients listed for thyroid surgery were assigned into two groups. Group I (n = 19) received subcuticular preincision infiltration with 10 ml of bupivacaine (0.5%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…They concluded that this method was safe and effective. Bagul et al (12) infiltrated subcutaneous 10 mL of 0.5% bupivacaine preincisionally in thyroidectomy patients, and they found that pain scores were 33 and 50 in the bupivacaine-infiltrated and control groups, respectively, at first sixth hour, but there was not any difference at the 24 th hour. There was no requirement of morphine in the bupivacaine group, but it was 25% in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that this method was safe and effective. Bagul et al (12) infiltrated subcutaneous 10 mL of 0.5% bupivacaine preincisionally in thyroidectomy patients, and they found that pain scores were 33 and 50 in the bupivacaine-infiltrated and control groups, respectively, at first sixth hour, but there was not any difference at the 24 th hour. There was no requirement of morphine in the bupivacaine group, but it was 25% in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial by Bagul et al [23] found that preincision infiltration with local anesthetic provided easy access and scores in analgesic control postoperatively in patients undergoing thyroid surgery with no effects on bruising or cosmesis. Rawal et al [24] discovered that pain relief after ambulatory breast augmentation was superior with incisional patient-control regional analgesia under local anesthesia when compared to oral analgesic.…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of headache was an occipital headache. Gozal et al (6) and Bagul et al (21) reported that bupivacaine wound infiltration reduced postoperative pain and opioid demand in thyroid surgery. Han et al (24) reported that greater occipital nerve block with bupivacaine reduced occipital headache and posterior neck pain after thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are well-designed studies investigating postoperative pain control, such as local anesthetic wound infiltration (6,21), bilateral superficial cervical plexus block (7,22,23), and greater occipital nerve block (24) in thyroid surgery, but the efficacy of intravenous PCA (IV PCA) in thyroid surgery has not yet been assessed. The aim of this study was to compare the analgesic efficacy and side effects of three PCA regimens using fentanyl (opioid) and ketorolac (NSAID) and to determine the appropriate dosage of fentanyl and ketorolac in patients after thyroid surgery.…”
Section: Introductionmentioning
confidence: 99%